Mitigation and adaptation in polycentric systems: sources of power in the pursuit of collective goals. (28th June 2017) - Morrison, Tiffany H.; Adger, W. Neil; Brown, Katrina; Lemos, Maria Carmen; Huitema, Dave; Hughes, Terry P.
Abstract : Polycentric governance involves multiple actors at multiple scales beyond the state. The potential of polycentric governance for promoting both climate mitigation and adaptation is well established. Yet, dominant conceptualizations of polycentric governance pay scant attention to how power dynamics affect the structure and the outcomes of climate action. We review emerging evidence on power within polycentric and distributed governance across the climate, forestry, marine, coastal, urban, and water sectors, and relate them to established positions on power within research on federalism, decentralization, international relations, and networked governance. We develop a typology of design, pragmatic, and framing power that focuses on how and in whose interests power is mobilized to achieve outcomes. We propose that the conceptual model helps to explain power dynamics across different sectors and across both climate change mitigation and adaptation. Significant research challenges arising from the analysis include the measurement and monitoring of the outcomes of power asymmetries over time. WIREs Clim Change 2017, 8:e479. doi: 10.1002/wcc.479 This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Abstract : Sources of power in the pursuit of collective goals.